PEMBERIAN OTAGO HOME EXERCISE PROGRAMME LEBIH BAIK DALAM MENGURANGI RISIKO JATUH DARIPADA BALANCE STRATEGY EXERCISE PADA LANSIA DI TABANAN - I Gede Putu Wahyu Mahendra; Ni Luh Nopi Andayani; I Made Krisna Dinata (Majalah Ilmiah Fisioterapi Indonesia, 2016)
ABSTRACTOne of the physical disorders that often occurs in the elderly is falling, beacuse of that, it need effort to reduce the risk of falling by training with otago home exercise program and balance strategy exercise for reducing falling risk in the elderly in Tabanan.This research was a randomized experimental design with pre and post test control group design. The sampling technique was simple random sampling. Samples were 30 elderly who were divided into 2 groups with 15 persons in each group: the treatment group received otago home exercise program and the controlgroup received balance strategy exercise. The result showed a significant difference in the treatment group and control group in which p=0,000 (p<0,05) with 25,16% in the treatment group and 12,80% in the control group. Based on the result of this study, it can be concluded that Otago home exercise programme is better for reducing falling risk than the balance strategy exercise in the elderly in tabanan. Keywords: Risk of fall, Otago Home Exercise Programme, Balance Strategy Exercsise, Timed Up And GO Test (TUGT)